DUAL TREE HUFFMAN ENCODING IMPLEMENTATION TO REDUCE LOW FREQUENCY BIT CODES - Tommy Tommy (INFOKUM, 2021)
Huffman encoding is a compression algorithm that uses symbol encoding using a simpler bit substitution based on the frequency of the symbol. A symbol will be represented with much fewer bits if it has a large frequency. Conversely, symbols with less frequency will be encoded with bits of greater length. The bit code for symbols with lower frequencies often has a very long size which sometimes causes the compressed file size to be larger than the original file. This study develops the implementation of two separate Huffman trees by dividing the symbol list into two lists, each of which will form a bit code in parallel. This implementation is able to minimize the length of the symbol bit code, especially in symbols with low frequencies so as to increase the compression ratio for several types of content which is become the weakness of the original Huffman.